Cincinnato Baruzzi perduto (?) - Mampieri, Antonella (MDCCC 1800, 2015)
Many works by the 19th century Italian sculptor Cincinnato Baruzzi are presently lost, destroyed or only mentioned by documents. Some of these sculptures are visually documented by drawings, photographs and book illustrations. The most interesting examples are: the models for the two funerary monuments sculpted for the Polish noble family Pac, formerly in Imola; the first version of Love capturing a soul, one of the earliest original creations of Baruzzi, replicated several times for British and German collectors; the Timpanista or Euterpe, a statue originally created for Elisa Fagnani Arese together with the destroyed memory of her two daughters and little granddaughter, formerly in the Arese villa in Sesto Milanese, documented by a drawing; the Sulamite commissioned by the well known Lombard patron Francesco Cavezzali for his villa in Lodi, a photograph of which was taken in its original surround in the forties; and some of Baruzzi’s statues, only described in letters and documents, whose image is preserved through the early photographic campaign commissioned by the sculptor from one of the first daguerreotype photographers, the Swiss Henry Béguin.